The promise and perils of produced waters: intelligent trial and error as an anticipatory framework for enabling responsible innovation. Issue 3 (2nd September 2019) - Dotson, Taylor C.
ABSTRACT: Human population increases alongside climatic changes has spurred interest in technologies exploiting unconventional water resources. However, analysis of the hazards entailed by these technologies has lagged behind research on their scientific and technical facets. This paper considers one unconventional resource: the waters resulting from oil and gas extraction processes-'produced waters.' This paper redeploys the Intelligent Trial and Error perspective on technological risk as an anticipatory framework, examining the question 'How amenable is the sociotechnical landscape of produced waters to learning of, averting, and responding to negative unintended consequences?' Controversy over recycling oil and gas wastewater for irrigation in Kern County, CA is analyzed as emblematic of the cultural, technical, and political barriers to responsible produced water innovation more broadly. This article shows how Intelligent Trial and Error can enhance the Responsible Research and Innovation framework with regard to addressing the material and political obstacles to more responsible R&D.